The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jped.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Heliox delivered by high flow nasal cannula improves oxygenation in infants with respiratory syncytial virus acute bronchiolitis

Abstract: Transient improvement of oxygenation in infants with RSV acute bronchiolitis during the initial phase of the therapy is associated with heliox when provided with HFNC, may provide a precious time for other therapeutic agents to work or for the disease to resolve naturally, avoiding other aggressive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…Future studies should determine whether heliox might help to improve low StO 2 in patients with severe respiratory failure. Although there are studies on heliox MV only single publications report on non-invasive respiratory support and the influence of the therapy on oxygenation in infants 27 , 28 . In the presented study the increase in SpO 2 values after 1 h of heliox was statistically significant but very subtle—most likely of limited clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should determine whether heliox might help to improve low StO 2 in patients with severe respiratory failure. Although there are studies on heliox MV only single publications report on non-invasive respiratory support and the influence of the therapy on oxygenation in infants 27 , 28 . In the presented study the increase in SpO 2 values after 1 h of heliox was statistically significant but very subtle—most likely of limited clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 22 were further assessed in the full-text phase. Six RCTs were found, [12][13][14][15]17,18 and all of these were included in the final analysis. We did not find any additional studies from other sources to be included (the references of the included studies were checked; see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…14,15 A previous meta-analysis conducted in 2015 stated that heliox does not increase the rate of discharge from the emergency department, decrease the rates of intubation, but it may decrease the length of stay in infants severe respiratory distress and receiving CPAP, but it must be noted that the quality of the included studies was classified as low and the meta-analysis included both parallel and crossover designed studies. 16 Since then, other studies on the use of heliox as a treatment for bronchiolitis 17,18 have been published. Thus, we decided to update the evidence summary.…”
Section: Introductionmentioning
confidence: 99%
“…Heliox did not reduce the risk of intubation, rate of emergency department discharge or length of treatment for respiratory distress. However, in infants on nCPAP right from the start helium-oxygen reduced the length of treatment: MD −0.76 days (95% CI −1.45 to −0.08, one trial, 21 infants, low quality evidence) ( 35 ). Chowdury et al concluded that “Heliox therapy does not reduce length of treatment unless given via a tight-fitting facemask or CPAP” ( 36 ).…”
Section: Clinical Applications Of Helioxmentioning
confidence: 99%